Development of inflammation-induced hyperalgesia and allodynia is associated with the upregulation of extrasynaptic AMPA receptors in tonically firing lamina II dorsal horn neurons - Kopach, Olga; Viatchenko-Karpinski, Viacheslav; Belan, Pavel; Voitenko, Nana (Frontiers in Physiology, 2012)
Persistent peripheral inflammation changes AMPA receptor (AMPAR) trafficking in dorsal horn neurons by promoting internalization of GluR2-containing, Ca2+-impermeable AMPARs from the synapses and by increasing insertion of GluR1-containing, Ca2+-permeable AMPARs in extrasynaptic plasma membrane. These changes contribute to the maintenance of persistent inflammatory pain. However, much less is known about AMPAR trafficking during development of persistent inflammatory pain and direct studies of extrasynaptic AMPARs functioning during this period are still lacking. Using Complete Freund’s adjuvant (CFA)-induced model of long-lasting peripheral inflammation, we showed that remarkable hyperalgesia and allodynia developes in 1–3 h after intraplantar CFA injection. By utilizing patch-clamp recording combined with Ca2+ imaging, we found a significant upregulation of extrasynaptic AMPARs in substantia gelatinosa (SG) neurons of the rat spinal cord 2–3 h after CFA injection. This upregulation was manifested as a robust increase in the amplitude of AMPAR-mediated currents 2–3 h post-CFA. These changes were observed specifically in SG neurons characterized by intrinsic tonic firing properties, but not in those that exhibited strong adaptation. Our results indicate that CFA-induced inflammation increases functional expression of extrasynaptic AMPARs in tonically firing SG neurons during development of pain hypersensitivity and that this increase may contribute to the development of peripheral persistent pain.